(3bUjOI aj PcQ GdTghQ hGdcQhe heG jUdM daUhd GdSfI ef GdCZPjIs - (3GdHMQ GdfYGeis ((3Ydi Hf CMeO Hf CHj jMji s)
(3ChdgG (B:s
(3CbGeJ cQhec ai TgQ BH ef GdeGA Jagb eKd GdLhGH ajGMHPG WfgG ai GdNQja EPG bgbgJ ai CYGdi GdgVGH s
(3BNQgG (B:s
(3hdYfI QHi Ydi GdeHZVjf YdjG hdbhG CTO GdYbGH JeJ GdbUjOI HMeO Gddg hefg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B43 - (3U(B46s
(3GfXQ GdbUjOI GdcejJjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B181 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs